First-line biological versus conventional synthetic disease-modifying antirheumatic drug therapy in adult-onset Still's disease: a multicentre, retrospective, propensity weighted cohort study - Kernder, Anna; Filla, Tim; Friedrich, Rhea; Blank, Norbert; Ernst, Diana; Henes, Jörg; Keyßer, Gernot; Klemm, Philipp; Krusche, Martin; Meinecke, Anna; Rech, Jürgen; Schulz, Nils; et al. (The Lancet Rheumatology, 2025)
Background: Data on the efficacy of biological disease-modifying antirheumatic drug (DMARD) therapies such as anakinra, canakinumab, and tocilizumab as a primary therapeutic option in adult-onset Still's disease (AOSD) are scarce, and treatment recommendations rely mainly on data extrapolated from paediatric studies. The aim of this study was to compare the effectiveness of first-line biological DMARD therapy versus conventional synthetic DMARD therapy in AOSD. Methods: This multicentre, retrospective, propensity weighted cohort study was done at 16 secondary and tertiary rheumatology centres across Germany. Eligible patients were diagnosed with AOSD, met the Yamaguchi classification criteria, and had active disease without current treatment. All patients had documented follow-up assessments at weeks 12 and 72. The primary endpoint was sustained, event-free remission; a combined endpoint of sustained remission (C-reactive protein <10 mg/L and no arthritis, rash, or fever) and absence of complications during follow up in patients treated with first-line biological DMARDs (with or without glucocorticoids) or conventional synthetic DMARDs (methotrexate or glucocorticoids). Analysis was by propensity score weighted logistic regression, thereby balancing for the initial Pouchot score, ferritin concentration, and age and sex differences between groups. Analysis was done in the per protocol population. People with lived experience were not involved in the study design. The study is registered with the ISRCTN registry, ISRCTN86135778. Findings: Between Jan 1, 2007, and Sep 30, 2022, we screened 228 patients for inclusion. 142 patients were excluded, and 86 patients with AOSD who had an incident diagnosis or a flare without any maintenance treatment including glucocorticoids were enrolled and included in our analysis. 50 (58%) of 86 patients were female, 36 (42%) were male, and 84 (98%) were White. The mean age at inclusion was 39·4 years (SD 15·4). 44 (51%) of 86 had received a first-line biological DMARD and 42 (49%) received a first-line conventional synthetic DMARD. Biological DMARD therapy was associated with a greater likelihood of reaching the primary endpoint of sustained, event-free remission (OR 7·20, 95% CI 2·50–36·64; p=0·0007). At week 72, the rate of sustained, event-free remission was 50% (95% CI 34–65%; n=21) in the first-line biological DMARD group and 12% (3–23%; n=5) in the first-line conventional synthetic group. Glucocorticoid-related complications were more often described in the first-line conventional synthetic DMARD group (new-onset arterial hypertension [n=2] and glucocorticoid-related skin diseases [n=3]) versus none in the first-line biological DMARD group). Three (7%) of 42 patients in the conventional synthetic DMARD group died (two from macrophage activation syndrome, one unknown cause) versus none in the first-line biological DMARD group. Interpretation: First-line biological DMARD therapy in patients with AOSD showed a statistically significant association with sustained, event-free remission and fewer complications. Our findings highlight the potential of biologics to improve patient outcomes compared with conventional treatment options in AOSD. Funding: None.
CRIS-Team Scopus Importer:2025-04-11